Clinical validation of AWGC-defined cachexia in gastric cancer patients: impact on body composition and quality of life - Huang, Yan; Wu, Xi; Ge, Yan; Wang, Chen; Ding, Xin; Zuo, Junbo (Frontiers in Nutrition, 2025)
BackgroundThe Asian Working Group for Cachexia (AWGC) has released consensus criteria for diagnosing cachexia in Asians. Nevertheless, there is limited data regarding the application of these criteria in cancer patients. This study aimed to assess the changes in body composition and quality of life in gastric cancer (GC) patients with cachexia defined by the AWGC criteria.MethodsBody composition parameters were analyzed using CT images at the level of the third lumbar vertebra. The European Organization for Research and Treatment of Cancer Quality-of-Life Questionnaire-Core 30 (EORTC QLQ-C30) was used to evaluate health-related quality of life (HRQoL). The diagnosis of cachexia was according to the AWGC criteria and Fearon’s criteria.ResultsA total of 431 patients with GC was included in this study. Among them, 160 patients (37.1%) were diagnosed with cachexia according to the AWGC criteria and 166 patients (38.5%) were diagnosed with cachexia based on the Fearon’s criteria. The agreement between the two criteria for diagnosing cachexia was moderate (k = 0.477, p < 0.001). Patients with AWGC-cachexia had significantly lower skeletal muscle index (SMI), visceral fat index (VFI), and subcutaneous fat index (SFI) compared to those without (p < 0.001). The prevalence of poor HRQoL was notably higher in patients with AWGC-defined cachexia (78.12% vs. 33.21%, p < 0.001). Furthermore, AWGC-defined cachexia was independently associated with poor HRQoL (OR = 5.92, 95% CI: 3.27–10.73; p < 0.001), while Fearon-defined cachexia did not show such an association (OR = 1.51, 95% CI: 0.86–2.65; p = 0.154).ConclusionPatients with AWGC-defined cachexia showed significant changes in body composition and was independently associated with poor HRQoL.